The Effectiveness of Development Performance in Gorontalo Province Over Two Cycles of RPJMD (2012-2022) - Baruwadi, Mahludin H.; Humalanggi, Mahyudin; Akib, Fitri Hadi Yulia; Hippy, Mohammad Zubair; Lantepon, Nancy N.; Butolo, Ivana (Jambura Equilibrium Journal, 2024)
This research aims to: 1) analyze the effectiveness of development performance achievements in Gorontalo Province over two cycles: RPJMD in 2012-2017 and RPJMD in 2017-2022; and 2) formulate recommendations for the effective achievement of development targets. The method employed was a survey utilizing secondary data in the form of time series with documentation data collection instruments. The effectiveness of development achievements was analyzed using descriptive statistics, and data were presented in tables, figures, and graphs. The effectiveness of development achievements was examined based on the trend of main development indicators in the two RPJMD cycles of Gorontalo Province from 2012-2017 and 2017-2022 and compared with the set targets. The research findings indicate that the development performance of Gorontalo Province during the period 2012-2022 reflects diverse dynamics. Economic growth experienced fluctuations with an initial surge in 2012 and the negative impact of the COVID-19 pandemic in 2020. The Human Development Index showed improvement, indicating efforts to enhance social conditions and the population's welfare, although it remains within the moderate category. The agricultural sector changed with increased maize production due to the Agropolitan program, but further efforts are needed to improve farmers' income and rural economic diversification. Surveys on community satisfaction revealed improvements in the quality of public services and governance and accountability enhancements. Despite positive achievements, Gorontalo Province still faces challenges in achieving better and sustainable performance in improving community welfare.